SARS-CoV2 vertical transmission with adverse effects on the newborn revealed through integrated immunohistochemical, electron microscopy and molecular analyses of Placenta - Facchetti, Fabio; Bugatti, Mattia; Drera, Emma; Tripodo, Claudio; Sartori, Enrico; Cancila, Valeria; Papaccio, Marta; Castellani, Roberta; Casola, Stefano; Boniotti, Maria Beatrice; Cavadini, Patrizia; Lavazza, Antonio (EBioMedicine, 2020)
. The occurrence of trans-placental transmission of severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) infection remains highly debated. Placental positivity for SARS-CoV-2 has been reported in selected cases, but infection or virus-associated disease of fetal tissues or newborns remains to be demonstrated. We screened for SARS-CoV-2 spike (S) protein expression placentas from 101 women who delivered between February 7 and May 15, 2020, including 15 tested positive for SARS-CoV-2 RNA, 34 tested negative, and 52 not evaluated as they did not meet testing criteria (32), or delivered before COVID-19 pandemic declaration (20). Immunostain for SARS-CoV-2 nucleocapsid (N) was performed in the placentas of all COVID-19 positive women. One placenta resulted positive for the SARS-CoV-2 S and N proteins, which was further studied by RNA-in situ hybridization and RT-PCR for S transcripts, and by electron microscopy. A comprehensive immunohistochemical and immunofluorescence analysis of the placental inflammatory infiltrate completed the investigations. SARS-CoV-2 S and N proteins were strongly expressed in the placenta of a COVID-19 pregnant woman whose newborn tested positive for viral RNA and developed COVID-19 pneumonia soon after birth. SARS-CoV-2 antigens, RNA and/or particles morphologically consistent with coronavirus were identified in villous syncytiotrophoblast, endothelial cells, fibroblasts, in maternal macrophages, and in Hofbauer cells and fetal intravascular mononuclear cells. The placenta intervillous inflammatory infiltrate consisted of neutrophils and monocyte-macrophages expressing activation markers. Absence of villitis was associated with an increase in the number of Hofbauer cells, which expressed PD-L1. Scattered neutrophil extracellular traps (NETs) were identified by immunofluorescence. We provide first-time evidence for maternal-fetal transmission of SARS-CoV-2, likely propagated by circulating virus-infected fetal mononuclear cells. Placenta infection was associated with recruitment of maternal inflammatory cells in the intervillous space, without villitis. PD-L1 expression in syncytiotrophoblast and Hofbaeur cells, together with limited production of NETs, may have prevented immune cell-driven placental damage, ensuring sufficient maternal-fetus nutrient exchanges.